Behavioral patterns of research on innovation in Cuba in the Web of Science 2010-2022 - Stable-Rodríguez, Yudayly (2025)
The behavior of innovation, which affects the productive structures of countries, has become an essential element for the development of scientific policies, aimed at its integral development in relation to society. In this sense, the behavioral patterns of research on innovation in Cuba, registered in the Web of Science, are evaluated based on the use of bibliometric indicators of production, collaboration and impact, and the contribution of this research to the Sustainable Development Objectives, in the period 2010 until 2022. The results showed an average annual growth rate of 36.6% in mainly national journals, with a co-authorship rate of 3.14 authors per document, indicating little association in contributions. The most important terms are related to evaluation and participation in innovation processes. The results contribute to the management of the country's science, technology and innovation policy, and can be input for the generation of new knowledge.